Early adoption of Arachis pintoi in the humid tropics: The case of dual-purpose livestock systems in Caquetá, Colombia - Rivas Ríos, Libardo; Holmann, Federico J. (2000)
The early adoption of the legume Arachis pintoi was studied in the State of Caquetá, located in Colombia’s Amazon region. Data came from 174 farmers randomly surveyed within the area of influence of Nestlé, a multinational milk-processing company. In addition, 52 farmers who had already adopted Arachis were surveyed separately to study their experiences, difficulties, and prospects with the legume. Results indicated that livestock activity is undergoing dynamic intensification. Since 1986, milk production per lactation has increased by 31%, cow fertility by 5%, herd size by 18%, and the area sown to improved pastures by 165%. Current adoption rate of Arachis is about 9.2%, with an estimated 3000 ha already planted. Two-thirds of farmers who had adopted Arachis said they would double, in the next year, the average area sown (9.6 ha/farm). Adopters tended to have larger farms and to have invested twice the capital than did non-adopters. The cost of seed for both grass and legume accounted for 40-52% of total establishment costs, making seed quality decisive in guaranteeing success. To promote Arachis, more information on the plant and its management in association with grasses must be disseminated. Mechanisms should also be sought to reduce establishment costs.